Dietary risk factors and cancer mortality burden from 1990 to 2021: a comparative study of China and global regions with varying sociodemographic development levels based on the Global Burden of Disease database - Zhao, Chunxiu; Ruan, Qian; Xiang, Bingbing; Zhang, Xuehe; Yang, Pingliang; Wang, Shun (Frontiers in Nutrition, 2025)
ObjectiveTo analyze temporal trends of diet-attributable cancer mortality in China (1990–2021), compare patterns between China and regions with varying development levels, and explore gender-specific characteristics to inform targeted prevention strategies.Study designCross-sectional and time-series analyses.MethodsWe conducted cross-sectional and time-series analyses of nine dietary risk factors across China, the global region, and five Socio-demographic Index (SDI) - stratified regions. Joinpoint regression models quantified temporal trends through Annual Percent Change (APC) and Average Annual Percent Change (AAPC).ResultsDiet-attributable cancer deaths in China decreased from 9.9% (95% CI: 2.2–20.5%) to 6.3% (95% CI: 2.1–12.8%) during 1990–2021. China’s 2021 attribution (6.3%) was below the global average (6.8%), exceeding high-SDI regions (5.8%) but below middle-SDI regions (7.4%). Low vegetable intake showed the largest decline (3.0 to 0.3%), while high red meat consumption increased (1.6 to 2.0%). Red meat’s impact was greater in females, while inadequate plant consumption affected males more significantly. Dietary factors most influenced colorectal cancer in China (39.2%). China’s diet-attributable cancer mortality decreased by 53.0% (from 18.4 to 8.7 per 100,000), exceeding global reductions (35.5%).ConclusionThis study identified distinct regional patterns in diet-attributable cancer mortality. China’s profile reflects its transition between development levels—decreasing vegetable-deficiency risks while increasing red meat consumption. Globally, attribution patterns are shifting from plant food inadequacy toward animal product excess, with persistent gender disparities.